Trypanosoma brucei Homologue of Regulator of Ribosome Synthesis 1 (Rrs1) Has Direct Interactions with Essential Trypanosome-Specific Proteins - Jaremko, Daniel (mSphere, 2019)
Studies in eukaryotic ribosome biogenesis have largely been performed in yeast, where they have described a highly complex process involving numerous protein and RNA components. Due to the complexity and crucial nature of this process, a number of checkpoints are necessary to ensure that only properly assembled ribosomes are released into the cytoplasm. Assembly of the 5S ribonucleoprotein (RNP) complex is one of these checkpoints for late-stage 60S subunit maturation. Studies in Saccharomyces cerevisiae have identified the 5S rRNA and four proteins, L5, L11, Rpf2, and Rrs1, as comprising the ribosome-associated 5S RNP. Work from our laboratory has shown that in the eukaryotic pathogen Trypanosoma brucei, the 5S RNP includes trypanosome-specific proteins P34/P37, as well as homologues of L5, Rpf2, and 5S rRNA. In this study, we examine a homologue of Rrs1 and identify it as an additional member of the T. brucei 5S RNP. Using RNA interference, we show that TbRrs1 is essential for the survival of T. brucei and has an important role in ribosome subunit formation and, together with TbRpf2, plays a role in 25/28S and 5.8S rRNA processing. We further show that TbRrs1 is a member of the T. brucei 5S RNP through the identification of novel direct interactions with P34/P37 and 5S rRNA as well as with TbL5 and TbRpf2. These unique characteristics of TbRrs1 highlight the importance of studying ribosome biogenesis in the context of diverse organisms and identify interactions that could be targeted for future drug development. IMPORTANCE Trypanosoma brucei is a parasite responsible for human and animal African trypanosomiasis. Current treatments for these diseases have numerous problems, and the development of novel chemotherapeutics can be achieved by identifying targets that are parasite specific and part of essential processes. Ribosome biogenesis is the process of generating translation-competent ribosomes and is critical for survival in all organisms. Work from our laboratory has shown that the formation of the 5S RNP, a crucial checkpoint in ribosome biogenesis, requires trypanosome-specific proteins P34/P37 and homologues of Rpf2 and L5 which possess parasite-specific characteristics. In this study, we characterize TbRrs1, an additional member of the T. brucei 5S RNP, and show that it is essential for parasite survival and has unique interactions with P34/P37 and 5S rRNA. This expands our understanding of the 5S RNP in T. brucei and identifies new targets for future drug development.